Combination of CT-Guided Microwave Ablation and Cementoplasty as a Minimally Invasive Limb-Sparing Approach in a Dog with Appendicular Osteosarcoma - David Sayag; David Jacques; Florence Thierry; Yoann Castell; Marcel Aumann; Olivier Gauthier; Vincent Wavreille; Lambros Tselikas (Animals, 2023)
Image-guided microwave ablation and cementoplasty are minimally invasive techniques that have been used as part of a limb-sparing approach in the treatment of appendicular bone tumors in humans. The objective of this case report was to describe the feasibility and result of microwave ablation (MWA) and cementoplasty in a dog with stage-1 osteoblastic appendicular osteosarcoma of the right distal radius. A microwave antenna was inserted in the osteolytic area using computed tomography (CT) guidance. Three ablation cycles of 5 min at 60 watts were performed. Immediately after the MWA procedure, a tricalcium phosphate-based cement was injected through the bone trocar to consolidate the ablated zone. Adjuvant chemotherapy with six sessions of carboplatin was performed, without major complication. Response to the treatment was evaluated according to RECIST criteria every 6 weeks. Twenty-four hours after MWA, the dog was pain-free and had excellent mobility. Based on CT measurements, a reduction of the size of the lytic area was observed at the 2-month and at the 7-month follow-up (from 13% to 25% of the longest diameter), classified as stable disease according to RECIST criteria. The dog died 18 months after the initial diagnosis due to distant metastases.